Detachment fold duplexes within gravity-driven fold and thrust systems. (January 2021) - Alsop, G.I.; Weinberger, R.; Marco, S.; Levi, T.
Abstract: Fold duplexes transfer displacement from a lower to an upper bounding detachment system via trains of folds with broadly parallel geometries. While they have been previously recognised in orogenic systems where they are considered to be kinematically equivalent to imbricating thrust ramps, we here describe the first example from a gravity-driven fold and thrust system (FATS) developed within late-Pleistocene mass transport deposits (MTDs) that formed around the Dead Sea Basin. The recognition in this study of basal and upper detachments that bound the FATS, together with later thrust ramps that imbricate the previously folded sequence, indicates that a fold duplex model is applicable in this case. Truncation of synclinal hinges, together with trapping of duplex roof stratigraphy in synclinal fold cores indicates that initiation of buckling precedes detachments, which then propagated along the upper and lower boundaries of the FATS to create a fold duplex. Downslope-verging folds, which are bound by the detachments, are subsequently cut by thrust ramps with greatest displacement recorded where ramps branch from the basal detachment. As thrust displacement increases then ramp angles generally reduce, which allows thrusts to continue to move and accrue larger displacements. Sequential flattening of lower thrusts in overstep sequences may create apparent 'back-steepening' up the slope in what superficially resembles 'pseudo-piggyback' sequences. Flattening of thrusts is achieved through tightening, rotation and expulsion of wet sediment and fluid from the cores of footwall synclines and is a consequence of loading from overlying thrust sheets. We speculate that expelled fluids may pond directly beneath overlying detrital-rich units that act as baffles and locally increase fluid pressures thereby facilitating further movement along the upper detachment. We establish a new model, whereby the vergence of structures formed above the upper detachment depends on the relative rates of roof and FATS translation, with slower downslope translation of the roof generating upslope verging folds in a 'sub-active' roof, while more rapid movement of a 'super-active' roof creates downslope verging folds. The observation that such patterns of minor fold vergence in the roof still largely correspond with the position of folds and thrusts in the underlying FATS indicates that only limited relative translation subsequently occurred between the roof and the FATS. This suggests that displacement must have transferred upwards to new upper detachments shortly after the folds in the roof were created, thereby 'fixing' the spatial correlation. As older detachments are folded and 'lock up', displacement migrates to new upper detachments that develop along pristine 'easy-slip' laminations at higher stratigraphic levels, thereby thickening the deforming FATS towards the sediment free surface. The creation of these new upper detachments at higher stratigraphic levels, together with the development of local overstep imbricate sequences are the principal differences between fold duplexes observed in orogenic settings and those in surficial gravity-driven FATS. Graphical abstract: Image 1